Mineralization of gold nanoparticles using tailored M13 phages. Issue 4 (1st December 2013) - Rothenstein, Dirk; Hans, Patrick; Srot, Vesna; van Aken, Peter A.; Bill, Joachim; Facey, Sandra J.; Ploss, Martin; Hauer, Bernhard; Melcher, Melanie
Abstract : The genetic engineering of M13 phage coat proteins provides an excellent system for the generation of functionalized biotemplates for the mineralization of inorganic materials in the nanometer range. Such biotemplates open facile synthesis approaches for the fabrication of miniaturized devices. The gold-binding peptide A3 was expressed at two different locations on the M13 particle surface, obtaining functionalized biotemplates with either gold-binding peptides at the one end or along the whole phage particle, respectively. The functionality of the gold-binding peptides fused to the respective phage coat proteins was tested by a binding assay with colloidal gold particles and confirmed by transmission electron microscopy. The engineered phage templates have a high affinity to gold compared with non-modified M13 phages. The binding strength is correlated to the number of expressed gold-binding peptides on the M13 phage particles. Gold nanoparticles (GNPs) were mineralized from chloroauric acid solutions. There, the M13 templates controlled the shape of the mineralized GNPs and the kinetic of the mineralization reaction. In the presence of M13 templates, GNPs were mineralized at the sites where the gold-binding peptides are localized. This approach shows a facile method for the localized mineralization of GNPs under the control of functionalized biotemplates.